Deciding to stop work or deciding how work is done?. (September 2021) - Havinga, Jop; Bancroft, Kym; Rae, Andrew
Highlights: Stop work decisions were about how to do work, rather than preventing accidents. Stop work decisions were common, unlike what associated interventions imply. Procedures rarely led to stopping work, as procedures rarely changed conditions of work. Abstract: Stopping work when work becomes unsafe is universally considered to be a positive safety behaviour. Safety interventions aimed at building the capability to stop unsafe work have focussed on assertiveness training and creating authority to stop work policies. A recent focus group-based study found that these interventions do not necessarily capture the most common factors influencing stop work decisions, and found that stop-work decisions can be enacted in different forms. Inspired by this work, we used an ethnographic study in a water utility provider to understand how decisions to stop work were made, and how they were influenced by procedures. In this organisation, crews frequently made decisions to stop work, usually by handing over the job to another crew. The decisions were easy to make if they could be framed as finding the best way to complete the job. Operators did not view decisions framed this way as safety related decisions. Procedures could cause crews to consider stopping work, but were unlikely to actually lead to a decision to stop work. If a crew considered it impossible to comply with a procedure, the crew who would pick up the cancelled job would likely encounter the same situation. As such, stopping work for procedural requirements was not perceived as improving safety. These findings challenge the idea that stop-work decisions are best supported through procedures, assertiveness training, and authority to stop work policies. As an alternative, the results suggest that organisations can influence workers to stop work by providing alternative methods for them to complete a job which crews themselves can arrange.